Selective 1, 4-arylsulfonation of 1, 3-enynes via photoredox/nickel dual catalysis. Issue 3 (24th December 2021) - Li, Chao; Hu, Duo-Duo; Jin, Ruo-Xing; Wu, Bing-Bing; Wang, Cheng-Yu; Ke, Zhuofeng; Wang, Xi-Sheng
Abstract : A photoredox/nickel-catalyzed selective 1, 4-arylsulfonation of 1, 3-enynes to access structurally diverse sulfone-containing allenes has been established with low catalyst loading. Abstract : A photoredox/nickel-catalyzed selective 1, 4-arylsulfonation of 1, 3-enynes to access structurally diverse sulfone-containing allenes has been established. This radical cascade transformation featured easy manipulation, mild conditions, low catalyst loading, broad substrate scope, and large-scale synthesis. The preliminary mechanistic studies indicated a possible radical-relay process enabled by the radical capture of nickel(0) species.